Comparison of Smart Antenna Technique Based on Adaptive Antenna Systems and Switched Beam Systems - Tito Yuwono; Mahamod Ismail; Zuraidah Zainudin (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2004)
The continuous increment of mobile communication subscribers, require a highercapacity and spectrum efficiency of the cellular system especially in an urban area where thetraffic density is high. In order to accommodate the increasing number of subscribers, smartantenna technology is used to improve system’s performance, which could increase thenumber of call and data transmission as well as simplifying the networking management. Thebasic principle of a smart antenna is to control and reduce the effect of interference toprovide the user with the highest quality of uplink and downlink signal. This can be achievedby using narrow beams with signal processing capability at the base sites and to optimize itsradiation pattern, which automatically updated according to MS movement or as signalsconditions change. In this study, two types of smart antenna were considered, which are theswitched beam systems and adaptive antenna systems. The significant difference betweenthese two systems is from the beamforming point of view. The key part of this study is todevelop a simulator for adaptive antenna systems (AAS) and switched beam systems (SBS)based on GSM 900 in order to determine the factors that could affect network’s quality andcapacity. Simulation results of different techniques are compared and the performanceevaluations of C/I are discussed. Results show that the AAS gives a better performancecompared to SBS, with average improvement of C/I around 5 to 10 dB.Keywords: smart antenna, adaptive, switched beam,C/I